2006
DOI: 10.1016/s0022-5347(05)00065-0
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal Prostate Biopsy and Fiducial Marker Placement in a Standard 1.5T Magnetic Resonance Imaging Scanner

Abstract: Purpose:We investigated the accuracy and feasibility of a system that provides transrectal needle access to the prostate concurrent with 1.5 Tesla MRI which previously has not been possible. Materials and Methods: In 5 patients with previously diagnosed prostate cancer, MRI guided intraprostatic placement of gold fiducial markers (4 procedures) and/or prostate biopsy (3 procedures) was performed using local anesthesia. Results: Mean procedure duration was 76 minutes and all patients tolerated the intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…The errors and procedure times with the APT II system compare favorably to reported results (average in-plane biopsy error 2.7 mm and average procedure times of 76 min) that we achieved with the active tracking method in clinical trials using the APT-I system [1], [3]. The hybrid tracking method allows the APT II system to be used on any MRI scanner without extensive systems integration and calibration.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The errors and procedure times with the APT II system compare favorably to reported results (average in-plane biopsy error 2.7 mm and average procedure times of 76 min) that we achieved with the active tracking method in clinical trials using the APT-I system [1], [3]. The hybrid tracking method allows the APT II system to be used on any MRI scanner without extensive systems integration and calibration.…”
Section: Discussionsupporting
confidence: 78%
“…In [1], [3], [4], [29], [30], [34], and [35], the authors reported the development and clinical evaluation of an MRI-guided system for transrectal prostate biopsies, therapy injection, and marker placements. The system, called the APT I, contains a single-loop MRI endorectal imaging coil and employs active tracking for device localization.…”
Section: Prostate Cancer Diagnosis and Therapymentioning
confidence: 99%
“…A manually operated version of this device has been used in clinical trials [11, 34]. Manually operated devices [10] have been the first to clinical tests and had major contributions to test the feasibility of interventional MRI.…”
Section: Kinematic Structurementioning
confidence: 99%
“…A few groups investigated the use of manually operated needle-guide devices in the MRI scanner [10, 11]. But these manual devices may be difficult to operate due to the limited access within the scanner and table movements are required to access the patient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation